Pengembangan Multimedia Interaktif Untuk Pembelajaran Sejarah Indonesia Dengan Metode Think Pair Share Pada Kelas X Smk Nh Multimedia Poncokusumo - Ojat, Achmad Darojat; Edo, Armedo Futhi Munadzar (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
Every teaching and learning activity the potential of media cannot be ignored, and often the object to be studied is too complex. This study aims to develop an interactive multimedia lesson on Indonesian History that has been validated for Tenth Grade SMK NH Multimedia Poncokusumo. In the trial activity, this Interactive Multimedia is combined with the Think Pair Share learning model, the learning activities will be even more interesting because it is different from conventional multimedia learning. The test results for developing interactive multimedia on media experts are 91.3% (valid). Data The results of testing the validity and development of the Interactive Multimedia method on material experts are 93% (valid). Meanwhile, the data from the test results of the validity and development of the Interactive Multimedia method on the audience or respondents are 95% (valid), the results of the small group audience trial are 92% (valid), and the learning outcomes test is 100% (effective). Overall, based on the product eligibility criteria, it can be concluded that the learning media is included in a valid statement, so it is feasible and effective to use in learning.